Intracranial Imaging of Uncommon Diseases Is More Frequently Reported in Clinical Publications Than in Radiology Publications - Lehman, V.T. (AJNR Am J Neuroradiol, 2014)
BACKGROUND AND PURPOSE: Descriptions of uncommon diseases with intracranial imaging abnormalities are often difficult to find in the radiology literature. We hypothesized that reported imaging findings of such conditions in the recent literature were more frequent in clinical compared with radiology journals. MATERIALS AND METHODS: PubMed searches from December 1, 2007 to December 1, 2012 were performed for 5 uncommon CNS diseases with intracranial imaging manifestations: 1) Susac syndrome; 2) amyloid β–related angiitis; 3) Parry-Romberg syndrome/en coup de sabre; 4) transient lesion of the splenium of the corpus callosum; and 5) reversible cerebral vasoconstriction syndrome. Articles were classified as a case report, case series, or original research. Journals were categorized as radiology or clinical. The 1- and 5-year Impact Factors of the journals were recorded. RESULTS: Two hundred two articles were identified for the 5 diseases, including 151 (74%) case reports, 26 case series (13%), and 25 original research articles (13%); 179 (89%) were published in nonradiology journals, compared with 23 (11%) in radiology journals. There was no significant difference between the mean 1- and 5-year Impact Factors of the radiology and clinical journals. CONCLUSIONS: Recent reports of the selected uncommon diseases with intracranial manifestations are more frequent in clinical journals when compared with dedicated radiology publications. Most publications are case reports. Radiologists should review both radiology and clinical journals when reviewing imaging features of uncommon diseases affecting the brain. Lack of reporting on such disease in the radiology literature may have significant practice, educational, and research implications for the radiology community.